Jealousy and Trust in Marriage: The Contribution of Cognitive Schemas and Marital Adjustment - Stanojević, Dragana Z.; Radović, Olivera B.; Jaredić, Biljana M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
Jealousy and trust are emotions that characterize many close relationships, particularly romantic ones, and can be influenced by various internal and external factors. This study examined whether—and to what extent—specific cognitive schemas and marital adjustment predict three aspects of jealousy, as well as trust in one’s partner. The sample consisted of 177 participants who were either formally or informally married, of whom 34.1% were men. Participants were aged 20–69 years (M = 41.49, SD = 8.90), and the length of the relationship ranged from 1 to 45 years (M = 13.57, SD = 9.08). Of the participants, 88.1% were formally married, while 11.9% were in a common-law union. The following instruments were used: the Multidimensional Jealousy Scale (Pfeiffer & Wong, 1989), the Trust Scale in Close Relationships (Larzelere & Huston, 1980), the Young Schema Questionnaire—Short Form (Young, 1998), and the Marital Adjustment Questionnaire (Ćubela Adorić, 2002). Results showed that the cognitive aspect of jealousy was predicted by emotional deprivation and marital adjustment, explaining 19% of the variance. The emotional aspect was predicted by insufficient self-control (3% of the variance), while the behavioral aspect was predicted by defectiveness/shame and mistrust/abuse schemas (5% of the variance). Trust in one’s partner was predicted by emotional deprivation, entitlement/ grandiosity, as well as marital adjustment. This model explained 41% of the variance in trust, with marital adjustment emerging as the most significant predictor, contributing independently to 23% of the variance. These findings suggest that established patterns of thinking and belief systems play a crucial role in shaping the emotional climate between partners, while marital dynamics—developed through mutual adjustment in various life domains—also significantly contribute. Psychotherapeutic interventions addressing both maladaptive cognitive patterns and dyadic functioning may enhance marital climate and overall relationship satisfaction.
Keywords: jealousy; trust; cognitive schemas; marital adjustment